2016
DOI: 10.1080/00220388.2016.1139692
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Loan Officers’ Work Experiences: Perspectives from Zambia

Abstract: The article studies the challenges faced by microfinance institutions in Zambia, whose remit it is to provide financial services to the poor. It focuses on loan officers -the agents of delivery on the ground. With reference to loan officers' experiences and words, the paper examines how gender and class shape and structure their day to day encounters. The study finds that different social spaces -'the office' and 'the field' -and wider context explains the gendered, culturally complex and multidimensional natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Thus, there is an incentive for group members to monitor the projects of one another to ensure that the loan is properly used to avoid repayment default. Additionally, group-based microfinance programs often rely on frequent interactions between loan officers and borrowers through regular visits and group meetings (Siwale 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is an incentive for group members to monitor the projects of one another to ensure that the loan is properly used to avoid repayment default. Additionally, group-based microfinance programs often rely on frequent interactions between loan officers and borrowers through regular visits and group meetings (Siwale 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, this suggests that local microfinance professionals without a business-related university degree can also play a significant role in terms of the provision of basic training and support to micro-entrepreneurs. Indeed, a recent study found that loan officers with lesser education find it easier to interact with the poor (Siwale 2016). Their mastery of the local context is an advantage.…”
Section: Provision Of Training and Support To Borrowersmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this, the Association of Microfinance Institutions of Zambia (AMIZ) and other sources (Brouwers et al. ; Siwale ) estimate that the industry's outreach is approximately 300,000 against potential demand of over 2 million people. Data from the Microfinance Information Exchange (MIX) shows that the microfinance sector in Zambia recorded 71,978 borrowers as at December 2015 and a gross loan portfolio of USD 6.5 million.…”
Section: The Microfinance Landscapes Of Nigeria and Zambiamentioning
confidence: 99%
“…Additionally, while the literature is limited, insight about the gender bias in the recruitment of microfinance credit officers shed light on the (adverse) strategies used by MFIs. A study by Siwale (2016) in Zambia reported higher recruitment of male credit officers in MFIs, as males were perceived as better able to coerce and instil fear amongst female borrowers. Furthermore, a study by Beck et al (2013) found that between male and female credit officers, female officers were better at building trust relationships, screening and monitoring of borrowers, and less problematic in handling loans.…”
Section: Negative Impacts Due To Microfinancementioning
confidence: 96%